KESEHATAN LINGKUNGAN DI DAERAH ALIRAN SUNGAI CIKAPUNDUNG AKIBAT PENCEMARAN AIR - Surtikanti, Hertien (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2005)
Cikapundung River, Bandung is headed from Bukit Tunggul. It is flowing down to the residential area of Bandung. Based on biological and chemical analysis, this river has been polluted due to domestic and industrial waste. So far, impact on human health due to this water pollution has not known. In order to obtain an information on human health, descriptive analysis including questionnare and intervieuw has been carried out at five study locations of Cikapundung Riveer (Bukit Tunggul, Maribaya, Babakan Siliwangi, Babakan Ciamis and Bojong Soang). The result from this study that respondents living at Bukit Tunggul, Maribaya and Babakan Siliwangi get the water from water supply and well. The three latest locations are polluted (Surtikanti, et al, 2002). They are not aware using river water for their essential need. However, their human health has to be paid attention, because diarrhoea, skin disease and fever dengue that related to water pollution were experienced by respondents. It indicates that water pollution of Cikapundung River has indirect impact to environmental health.Keywords: human health, water pollution, Cikapundung River, domestic- industrial waste.